Conformational changes in amyloid-beta (12–28) alloforms studied using action-FRET, IMS and molecular dynamics simulations1. Issue 8 (14th August 2015) - Daly, Steven; Kulesza, Alexander; Poussigue, Frederic; Simon, Anne-Laure; Choi, Chang Min; Knight, Geoffrey; Chirot, Fabien; MacAleese, Luke; Antoine, Rodolphe; Dugourd, Philippe
<x xml:space="preserve">Abstract</x> The gas phase conformations of two amyloid beta mutants are studied by multiple techniques to elucidate the origin of the different aggregation behaviour.